2002
DOI: 10.1098/rspb.2002.2017
|View full text |Cite
|
Sign up to set email alerts
|

Male phenotype predicts insemination success in guppies

Abstract: Theory predicts that mate choice can lead to an increase in female fecundity if the secondary sexual traits used by females to assess male quality covary with the number of sperm transferred during copulation. Where females mate multiply, such a relationship between male attractiveness and ejaculate size may, additionally (or alternatively), serve to augment the effect of indirect selection by biasing paternity in favour of preferred males. In either case, a positive correlation between male attractiveness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
88
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 37 publications
0
88
0
1
Order By: Relevance
“…Eighty-eight per cent of broods had one or two fathers (figure 3)-an observation consistent with post-copulatory sperm selection. How the winners of sperm competition are chosen remains unclear (but see Evans et al 2003b) although a recent investigation (Pilastro et al 2002) indicates that females may control the number of sperm inseminated during cooperative matings. Irrespective of the mechanisms involved, a sampling effect, whereby a different subset of available inseminates is used on each occasion, could account for the observed sire turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-eight per cent of broods had one or two fathers (figure 3)-an observation consistent with post-copulatory sperm selection. How the winners of sperm competition are chosen remains unclear (but see Evans et al 2003b) although a recent investigation (Pilastro et al 2002) indicates that females may control the number of sperm inseminated during cooperative matings. Irrespective of the mechanisms involved, a sampling effect, whereby a different subset of available inseminates is used on each occasion, could account for the observed sire turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies indicate that male phenotype covaries with sperm load (Matthews et al 1997;Pilastro & Bisazza 1999;Pitcher & Evans 2001) and that males with preferred phenotypes are likely to be favoured during post-copulatory sexual selection (Pilastro & Bisazza 1999;Evans & Magurran 2001;Pilastro et al 2002;Evans et al 2003; see also Pitcher et al 2003). Evans and Magurran (2000) found that offspring from multiply mated female guppies exhibited enhanced schooling abilities and better developed anti-predator escape responses than their singly sired counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Outside periods of female sexual receptivity, males have the potential to undermine precopulatory female choice using forced ''gonopodial thrusts'' (Pilastro and Bisazza 1999). Recent work reveals that phenotypically attractive males are more successful during sperm competition (Evans and Magurran 2001;Evans et al 2003) and inseminate higher numbers of sperm than their less ornamented counterparts (Pilastro et al 2002). Intriguingly, the latter study revealed that attractive males inseminated more sperm during solicited but not forced copulations, prompting us to suggest that females may influence the number of sperm inseminated in favor of phenotypically attractive males (Pilastro et al 2002).…”
mentioning
confidence: 99%
“…Recent work reveals that phenotypically attractive males are more successful during sperm competition (Evans and Magurran 2001;Evans et al 2003) and inseminate higher numbers of sperm than their less ornamented counterparts (Pilastro et al 2002). Intriguingly, the latter study revealed that attractive males inseminated more sperm during solicited but not forced copulations, prompting us to suggest that females may influence the number of sperm inseminated in favor of phenotypically attractive males (Pilastro et al 2002). The current study tests this hypothesis explicitly by determining whether the number of sperm transferred (or retained) during solicited copulations is influenced exclusively by the female's perception of male attractiveness, independent of any direct manipulation of the focal males themselves.…”
mentioning
confidence: 99%